A Study on the Prevalence of Peer Bullying Among Preschool Children: A Case Study of Wat Angthong Kindergarten School - Olanwat, Nutchanat; Masantiah, Chuthaphon; Tippayakulpairoj, Darunee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Bullying problems can occur at all ages and tend to become more severe with age. In early childhood, bullying can also occur. Few studies show that early childhood children can bully each other. This research study will make parents, teachers, and other stakeholders aware and give importance to solving this problem in the future. This research aims to investigate the prevalence of peer bullying among preschool children at Anuban Wat Angthong School. Methodology: It employs a case study approach within the mentioned school, gathering data from 547 students in kindergarten levels 1 to 3 during the academic year 2023. Classroom teachers serve as observers and assessors of student behaviors, with statistical analysis used to interpret the observed behaviors in terms of frequency and percentages. Results: The study found that the majority of preschool children at Anuban Wat Angthong School did not exhibit bullying behaviors in all three forms: physical, verbal, and social. Specifically, (1) physical bullying behaviors were observed in 68.20% to 94.50% of students across 10 sub-behaviors, (2) verbal bullying behaviors were observed in 88.10% to 95.60% of students across 8 sub-behaviors, and (3) social bullying behaviors were observed in 88.80% to 95.60% of students across 4 sub-behaviors. Conclusion: According to the study, while the majority of preschoolers at Anuban Wat Angthong School did not participate in bullying behaviors, a sizeable percentage did engage in physical, verbal, and social forms of bullying. Prevalence rates for these sub-behaviors ranged from 68.20% to 95.60%.